PENERAPAN PENDEKATAN PROBLEM POSING PEMBELAJARAN MATEMATIKA DI KELAS VIII A SMPN 2 TAMAN - Anna Wahyu Hidayah (Universitas PGRI Adi Buana Surabaya, 2016)
This research in the wake of the fact it can be said that the rapid technological development wasbased on the development of mathematics, math has been taught right from kindergarten up of a higher level.To print a future thinker with math experts needed for effective learning and efficientso that teachers should be able to select appropriate learning for students. formulation of the problem in this research is” how completeness of student learning outcomes, level of creative thinking abilitiesand the students' response to learning Problem Posing?” the purpose of this study was to describeclassically completeness of student learning outcome, level of creative thinking abilitiesand the students, and the response given students after learning Problem Posing.In this study to measure student mastery gained from achievement test(THB), to determine the level of students' creative thinking abilities(TKBKS) taken from the test results correlated learningwith components of creative thinkingthat is fluency, flexibility, originility, dan elaborationand to evaluate the response of the students was obtained from questionnaires source data from this study is the class VIII A SMPN 2 Taman. Data obtained from this study are as followsz: from the results THB stated that in the classical completeness of85,29 %,as much as 67 % students occupied TKBKS levelfour (very creative) and the students' response to the statement of learning Problem Posing have an average maximum of 3,51that is